Programa residência pedagógica: evidências de uma concepção de alfabetização da prática no chão da sala de aula - ARAÚJO, Camila Silva (2025)
This study, based on a research internship within the Pedagogical Residency Program, aims to analyze the pedagogical practices observed in a second-year elementary school class in a public school in Pará during the 2023 school year. The goal was to identify the main challenges and opportunities in pedagogical practice, as well as to discuss the importance of the partnership between family and school for the students’ overall development. In addition to observation, a "pedagogical intervention" was implemented to integrate theory and practice within the class. The research employed a qualitative methodology, using field journals and direct observations, focusing on Portuguese Language instruction and examining the interactions between teachers, knowledge, and students during the teaching and learning process. The data collected were analyzed to identify patterns in teaching practices. The study concluded that literacy instruction follows a traditional method, with a strong emphasis on grammar over semantics and contextual meaning. There is limited focus on fostering autonomy, creativity, and imagination in reading and writing practices. Despite challenges, the Pedagogical Residency Program provides a valuable opportunity for teacher training by promoting theory-practice interaction, offering pedagogy students practical experience in elementary schools. The study offers a critical and reflective perspective on the observed didactics, contributing to initial teacher education in pedagogy and supporting a meaningful and transformative professional practice.